2019
DOI: 10.1111/jgh.14605
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes after therapeutic endoscopic retrograde cholangiopancreatography using balloon‐assisted enteroscopy for anastomotic stenosis of choledochojejunostomy/pancreaticojejunostomy

Abstract: Background and Aim Data on long‐term outcomes after therapeutic endoscopic retrograde cholangiopancreatography (ERCP) using balloon‐assisted enteroscopy (BAE) for choledochojejunal anastomotic stenosis (CJS) or pancreaticojejunal anastomotic stenosis (PJS) remain limited. We retrospectively assessed the long‐term results of patients who achieved clinical success using BAE for CJS and PJS. Methods Patients who achieved technical and clinical success for CJS or PJS by BAE‐ERCP and were followed up for more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 35 publications
2
20
1
Order By: Relevance
“…With the popularization and development of BAE technology, ERCP in patients with a surgically altered anatomy is gradually increasing. [ 12 , 13 ] However, the use of these new endoscopes may lead to new difficulties and complications, such as previously unseen types of barotrauma in closed afferent intestinal limbs. There are currently no gold standard approaches for addressing biliopancreatic disorders in patients with a surgically altered anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…With the popularization and development of BAE technology, ERCP in patients with a surgically altered anatomy is gradually increasing. [ 12 , 13 ] However, the use of these new endoscopes may lead to new difficulties and complications, such as previously unseen types of barotrauma in closed afferent intestinal limbs. There are currently no gold standard approaches for addressing biliopancreatic disorders in patients with a surgically altered anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of JGH, Behary et al identified and validated six optical features used to differentiate benign from neoplastic biliary lesions assessed at balloon-assisted cholangioscopy (BAC), 1 while Sano et al reported that therapeutic endoscopic retrograde cholangiopancreatography (ERCP) using balloon-assisted enteroscopy (BAE) for anastomotic stenosis of choledocho-/ pancreaticojejunostomy could achieve long-term success rates comparable to percutaneous transhepatic treatment or surgical reanastomosis. 2 ERCP in patients with surgically altered anatomy has lower success and higher complication rates compared to ERCP in patients with normal anatomy. 3 Nonetheless, an endoscopic approach is considered less invasive and preferred over percutaneous transhepatic treatment and surgery.…”
Section: When the Balloon Goes Up …mentioning
confidence: 97%
“…identified and validated six optical features used to differentiate benign from neoplastic biliary lesions assessed at balloon‐assisted cholangioscopy (BAC), while Sano et al . reported that therapeutic endoscopic retrograde cholangiopancreatography (ERCP) using balloon‐assisted enteroscopy (BAE) for anastomotic stenosis of choledocho‐/pancreaticojejunostomy could achieve long‐term success rates comparable to percutaneous transhepatic treatment or surgical re‐anastomosis …”
mentioning
confidence: 99%
“…2c,d) (Video S1). Although most CJs are treatable by BE‐ERCP or EUS‐guided procedure, 2–5 some cases require other approaches. To avoid invasive surgery, the piercing technique for cases of complete obstruction of CJs and the percutaneous route for taking the correct direction are useful.…”
Section: Brief Explanationmentioning
confidence: 99%